Psychometric Properties of the SOC-13 Scale in Colombian Adults (2021)
The aim of this study was to determine the psychometric properties of the Spanish version of the SOC-13 in Colombian adults. The SOC-13 questionnaire was administered to 489 individuals aged ≥18 years who were in lockdown from March to July 2020 in Nariño County, Colombia. Psychometric properties of the scale were examined using a cross-validation method via exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Additionally, configural and metric invariance were tested. To determine the internal consistency of the questionnaire, McDonald’s omega (ω), Cronbach’s alpha (α), and composite reliability (CR) coefficients were estimated. The EFA determined that a three-factor structure best fit the data (comprehensibility, manageability, and meaningfulness) and CFA confirmed this three-factor model structure showing a good fit (χ2 S-B = 188.530, χ2 S-B/(62) = 3.615, p = 0.001; NNFI = 0.959; CFI = 0.968; RMSEA = 0.052 (90% CI [0.041–0.063]) and SRMR = 0.052). The invariance analysis indicated the same underlying theoretical structure between genders. Additionally, (ω), (α), and (CR) coefficients confirmed a high internal consistency of the instrument. The SOC-13 scale, reflecting comprehensibility, manageability, and meaningfulness, is a reliable and valid tool for assessing the sense of coherence in Colombian populations.